TINJAUAN TEORITIS DAN EMPIRIS EFISIENSI, RISIKO, DAN PERILAKU RISIKO USAHA TANI SERTA IMPLIKASINYA DALAM UPAYA PENCAPAIAN SWASEMBADA PANGAN (Forum Penelitian Agro Ekonomi, 2024)
This paper aims to describe various models and results of empirical analyses of efficiency, risk, and risk behavior of farming in the country and abroad. Efficiency analyses on food crops, horticulture, and processing industry scales show various technical efficiencies, and both economic and allocative inefficiencies. To support food self-efficiency, therefore it is necessary to improve farm business efficiency and to reduce risk farming. Government’s and non-government organizations’ aids are required to improve farm efficiencies, such as irrigation construction and maintenance, factor inputs distribution, credit access, agricultural insurance, and research results dissemination. To improve allocative and economic efficiencies, some efforts are necessary to take such as marketing infrastructure enhancement, acceleratin transport of agricultural inputs and products, and expanding farmers’ access for information.